A study of the attitudes of the local elites of Dungun on population and family planning / Ramlah Muda - Ramlah , Muda (1976)
Much of the world now faces severe social and economic problems resulting from rapid population growth. The South East Asian countries, including Malaysia are no exception. In 1976, the world’s population had already reached the 4 billion mark. Malaysia’s population alone is 10,500,000 which represents an increase of about two million since 1966. Such rapid population growth is an obstacle towards achieving better standard of living.